HUBUNGAN PENGETAHUAN IBU DAN STATUS GIZI ANAK DENGAN TINGKAT DEHIDRASI BALITA PENDERITA DIARE DI RUANG PERAWATAN ANAK RSUD LABUANG BAJI MAKASSAR - Mariati; Ady Iranas; Kiki Rizki Aulia (Akademi Kebidanan Harapan Bunda Bima, 2025)
Abstract Background : Diarrhea with dehydration in toddlers remains a major cause of child morbidity and mortality. This may be due to parents' inadequate implementation of early rehydration principles at home, leading to dehydration by the time they are brought to the health care facility. It may also be due to the child's physical condition during diarrhea, which is not optimal for nutritional support. Objective : This study aimed to determine factors associated with dehydration levels in toddlers with diarrhea. Method : This study used a descriptive analytical method with a cross-sectional approach. The study site was Ruang Perawatan Anak of Labuang Baji Hospital, Makassar. The sample was toddlers with diarrhea treated there. The sampling technique used was accidental sampling. Data were obtained from surveys, interviews, and direct observation upon patient arrival, as well as primary data from the Pediatric Ward of Labuang Baji Hospital. Hypotheses were tested using the Chi-square test with a p-value <0.05. Results : The results obtained during the study were a sample size of 32 respondents. The Fisher test analysis revealed a relationship between parental knowledge and dehydration levels with a p-value of <0.001 (<0.05), and a relationship between nutritional status and dehydration levels with a p-value of <0.001 (<0.05).